1987
DOI: 10.1248/cpb.35.4482
|View full text |Cite
|
Sign up to set email alerts
|

Purines. XXIX. Syntheses of 9-alkyl-2-deuterio-N6-methoxyadenines and 2-deuterio-N6,9-dimethyladenine: Tautomerism in 9-substituted N6-alkoxyadenines.

Abstract: Cyclizations of the alkoxyamidines 7a, i with formic acid gave N6-methoxy-9-methyladenine (8a) and 9-benzyl-N6-methoxyadenine (8i). Replacement of formic acid by formic-d acid-d in these cyclizations afforded the 2-deuterated species 13a and 13i. A similar cyclization of 22, obtained from 21 by alkaline hydrolysis, with formic-d acid-d yielded 2-deuterio-N6-methoxy-1,9-dimethyladenine (24). The N6-methyl isomer 19 was prepared from 13a by treatment with NaH and MeI.Comparison of the proton nuclear magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 2 publications
3
13
0
Order By: Relevance
“…-95 ppm in imines 2Ј (relative to MeNO 2 at 0 ppm), as reported for 2aЈ previously. [3] All iminopurines 2Ј are drawn with the NH at N-1 and in their most probable double bond configuration (syn, Scheme 2), in accordance with earlier NMR [3,10,11] and UV [10] studies of imine 2aЈ and other 6-(methoxyamino)purines. We have no indication that chromatographic separation of any of the tautomer pairs would be possible.…”
Section: Resultssupporting
confidence: 78%
“…-95 ppm in imines 2Ј (relative to MeNO 2 at 0 ppm), as reported for 2aЈ previously. [3] All iminopurines 2Ј are drawn with the NH at N-1 and in their most probable double bond configuration (syn, Scheme 2), in accordance with earlier NMR [3,10,11] and UV [10] studies of imine 2aЈ and other 6-(methoxyamino)purines. We have no indication that chromatographic separation of any of the tautomer pairs would be possible.…”
Section: Resultssupporting
confidence: 78%
“…In the case of an adenine derivative methoxylated at N(6), it has been shown that this modi®cation allows the adenine base to tautomerize between amino and imino forms with the latter more stabilized under hydrophilic conditions (Stolarski et al, 1984;Fujii et al, 1987). Matsuda and his colleagues showed by an in vitro polymerase incorporation assay that when a DNA fragment containing the modi®ed adenosine was used as a template, not only complementary thymidine residues but also cytidine residues were incorporated into the newly synthesized opposite DNA strand (Nishio et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The purine analogues N 6 -methoxyadenine (mo 6 A) (Z) and N 6 -methoxy-2,6-diaminopurine (K) correspondingly showed specific pairing with cytosine (C) and thymine (T) in duplexes (15)(16)(17). The analogue K gave greater duplex stabilities and so was chosen for further studies.…”
mentioning
confidence: 99%